PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH DAN MUSYARAKAH TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH (STUDI KASUS PADA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DAERAH ISTIMEWA YOGYAKARTA YANG TERDAFTAR DI OTORITAS JASA KEUANGAN PERIODE 2013-2015) - Davit Hidayatullah (JURNAL EKOBIS DEWANTARA, 2018)
Abstract The purpose of this study was to investigate and determine the financing Murabahah, Mudarabah, Musyarakah and profitability. The population in bank financing syariah people's Special Region of Yogyakarta registered the Financial Services Authority in the period 2013-2015. The study sample consisted of 3 bank syariah financing people PT. BPRS Dana Hidayatullah, PT Barokah Dana Sejahtera and PT. BPRS Madina Mandiri Sejahtera. The sampling technique used purposive sampling. The data in this study tested by statistical test, classic assumption test, and analyzed using multiple regression analysis. This analysis was used to determine whether the financing Murabahah, Mudarabah and Musyarakah effect on profitability either partially or simultaneously. Murabahah, Mudharabah and Musyarakah financing simultaneously have a positive effect on ROE profitability, p-value is 0.001. The p-value is less than the specified level of significance of 5%, In Murabahah financing t test partially have positive effect to ROE known that p-value <α (0,001 <0,05) meaning significant. Mudharabah financing is known that p-value> α (0.403> 0,05), which means no significant effect on ROE. Musyarakah financing is known that the value of p-value> α (0.422> 0.05) which means no significant effect on ROE. Murabahah, Mudharabah and Musyarakah financing to ROE level of 32.4%.